Economic-geographical position as a factor of regional development in Russia - Stepan Zemtsov; Vyacheslav Baburin (European Regional Science Association (ERSA), 2016)
The category of economic-geographical position (EGP) is one of the most common in regional science in Russia. N. Baranskiy firstly proposed the concept: 'EGP is an attitude of any place to other outside lying givens that have a particular economic significance. It is extremely important to a particular region to be in a short distance to main routes, markets and large centres'. The concept has become an important tool for regional and cross-country analysis, but it was suffering from a lack of formalization. An EGP may have a significant impact on a modern regional development. New automobile factories in Russia are located close to the largest and growing in 2000th consumer markets (Moscow and St. Petersburg, respectively). Poor development of distant Russian regions, as the Republic of Altai and the Tuva Republic, is related to their unfavourable landlocked position away from the main traffic flows and major economic centres. Thus, EGP is a probabilistic category, and its potential benefits can be realized depending on the regional policy, development of infrastructure and other factors. The aim of this work is to formalize the EGP category and assess the benefits (potential) of economic-geographical position in its relation to regional development in Russia. We formalized the concept in the paper according to a review of the corresponding scientific literature. We developed a method of assessment of international (EGP2) and interregional EGP (EGP1) potential based on the use of gravity models: EGPi = EGP1 + EGP2 = sum MVj/Rij^a where MVj -is gross regional product of a region j, or gross domestic product of a country j; Rij is an actual distance between regional and country capitals; a is an empirical coefficient, showing a speed of potential socio-economic interaction decrease between regions in accordance with increasing distance between them. The higher the EGP potential is, the more intensive interactions can be and the higher benefits for regions will be. These calculations for Russia's regions showed a significant spatial differentiation. The regions located near the Moscow and St. Petersburg agglomerations have the maximum interregional EGP potential, the potential decreases from these centres to the eastern Russian part. The maximum EGP² potential is concentrated in regions on a coast of the Black, the Baltic and the Sea of Japan. The total EGP potential of the Kaliningrad region is 5.6 times higher than it is for the Tyva Republic. We revealed a significant increase in the total EGP potential during the period of 1998-2000, and the potential shifted to the southern Far Eastern regions due to the growth of the Asia-Pacific economies. The favourable EGP is correlated with investment, foreign trade and migration growth and new technologies diffusion in the Russian regions. However, the role of different types of the EGP has changed during the period. The total EGP potential, according to the multivariable regression results, was a significant factor of a regional development in Russia. The EGP formalization allows using it as a method for externalities evaluation of infrastructural projects and to predict the spatial changes in the socio-economic development of Russia.
Keywords: O18; 330; economic-geographical position; market potential; the Russian regions; gravity models; regional development